2014
DOI: 10.1002/app.41716
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of the influence of pellet shape on single screw extrusion

Abstract: Extrusion technology is one of the most prominent methods for processing polymers. The shape of polymer pellets plays an important role in conveying solid material through the extruder and thus directly influences the mass flow rate. In the course of this article, the influence of the pellet shape of a polypropylene homopolymer on the processing conditions using a smooth barrel single‐screw extruder is evaluated. Especially the mass flow rate, the melt temperature, and the pressure build up in the barrel are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…3 They show that long cylindrical pellets exhibit a higher mass flow rate in all of the experiments while the counterpressure is comparable. For low screw speeds and high counterpressure, the achievable rise in the mass flow rate is 33%.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…3 They show that long cylindrical pellets exhibit a higher mass flow rate in all of the experiments while the counterpressure is comparable. For low screw speeds and high counterpressure, the achievable rise in the mass flow rate is 33%.…”
Section: Introductionmentioning
confidence: 94%
“…3,19 In the aforementioned previous study, a major effect of the pellet shape on the external frictional coefficient could be demonstrated when working at standard conditions on a screw tribometer. It was found that long cylindrical polypropylene pellets exhibit a higher ECOF than spheroidal pellets.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A previous work [14] has shown, that the throughput of SSE is strongly dependent on the geometry of the polymer bulk solids, at least when small screw diameters are used. It has been figured out that cylindrical pellets caused a much higher throughput than spheroidal ones.…”
Section: Introductionmentioning
confidence: 99%